Analysis of Clinical Characteristics, Treatment, and Prognostic Factors of 106 Breast Cancer Patients With Solitary Pulmonary Nodules - He, Lihong; Wang, Xiaorui; Liu, Xiaodong; Jia, Yongsheng; Zhao, Weipeng; Jia, Xiaochen; Zhu, Yuehong; Meng, Wenjing; Tong, Zhongsheng (Frontiers in Surgery, 2022)
【Abstract】 Objective To retrospectively analyze the clinical characteristics of breast cancer patients with solitary pulmonary nodules (SPN), compare the clinical characteristics of breast cancer patients with primary lung cancer (PLC) and metastatic pulmonary breast cancer (MBC), and analyze the treatment plan, efficacy and influencing factors. Methods A retrospective analysis of the clinical data of 106 SPN patients with breast cancer surgery in our hospital from January 2015 to June 2020. The characteristics of the patients' primary breast cancer lesions and the survival status of all patients during the follow-up period were recorded.Results Compared with MBC patients, PLC patients had statistically significant differences in onset age, interval, maximum nodule diameter, lymph node status, estrogen receptor (ER) expression, triple negative, and radiotherapy history (P<0.05). Of the 65 PLC patients, 23 patients underwent radical lobectomy+radiotherapy+chemotherapy, 39 patients underwent wedge resection+chemotherapy, and 3 patients underwent radiotherapy+chemotherapy. Of the 41 MBC patients, 13 patients underwent wedge resection plus endocrine therapy, 21 patients received radiotherapy plus chemotherapy plus endocrine therapy, and 7 patients received radiotherapy plus chemotherapy. The 1, 3 and 5 years overall survival rates of patients with PLC were higher than those of patients with MBC (P<0.05). Univariate analysis showed that the prognosis of patients with breast cancer combined with SPN was related to the interval, the presence of vascular tumor thrombus, the maximum diameter of the nodule, the type of SPN, and chemotherapy (P<0.05). Multivariate analysis showed that interval, vascular tumor thrombus, SPN type and chemotherapy were all independent factors affecting the prognosis of patients with breast cancer combined with SPN (P<0.05). Conclusion SPN in breast cancer patients combined with PLC and MBC, PLC patients and MBC patients have significant differences in pathological characteristics. Individualized treatment with priorities for patients with breast cancer combined with SPN can effectively improve the quality of life and prolong the survival time of patients. Interval, vascular tumor thrombus, SPN type and chemotherapy are all independent factors affecting the curative effect of patients with breast cancer combined with SPN.